2021
DOI: 10.1111/sjop.12710
|View full text |Cite
|
Sign up to set email alerts
|

Developing a non‐verbal, self‐report assessment tool of action tendencies: The Depicted Action Tendencies (DAT) instrument

Abstract: The objectives of this series of studies were to develop and evaluate a visual self‐report measure, the Depicted Action Tendencies (DAT), for the assessment of action tendencies, and to examine relations between action tendencies and emotions. In three independent studies, 938 participants evaluated drawings depicting individuals engaged in actions, reflecting four classes of action tendencies; the tendency to approach reward, approach threat, avoid threat, and avoid reward. The DAT instrument showed specifici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…Participants’ action tendencies were measured with a recently validated nonverbal pictorial measure: Depicted Action Tendencies (DAT; OToole & Mikkelsen, 2021 ). The DAT items portray characters engaged in actions reflecting four different action tendencies: approach a reward (e.g., running toward something meaningful/rewarding), approach a threat (e.g., confronting someone), avoid a reward (e.g., withdrawal from meaningful activities), or avoid a threat (e.g., fleeing from something or freezing; see Table 1 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Participants’ action tendencies were measured with a recently validated nonverbal pictorial measure: Depicted Action Tendencies (DAT; OToole & Mikkelsen, 2021 ). The DAT items portray characters engaged in actions reflecting four different action tendencies: approach a reward (e.g., running toward something meaningful/rewarding), approach a threat (e.g., confronting someone), avoid a reward (e.g., withdrawal from meaningful activities), or avoid a threat (e.g., fleeing from something or freezing; see Table 1 ).…”
Section: Methodsmentioning
confidence: 99%
“…Studies of bodily displays have frequently compared two sets of displays: expansive displays, which have often been associated with approach and engagement, and contractive displays, commonly associated with avoidance or withdrawal (O'Toole & Mikkelsen, 2021 ). Recently, a number of reviews and meta‐analyses have been conducted on the effect of expansive and contractive displays on affective, behavioral, and hormonal outcomes (Carney et al., 2015 ; Cesario et al., 2017 ; Cuddy et al., 2018 ; Elkjær et al., 2022 ; Körner & Schütz, 2020 ; Körner et al., 2022 ; Simmons & Simonsohn, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Recently it was suggested that emotions associated with opposing action tendencies (i.e., approach vs. avoidance) may counteract each other (Lutz & Krahé, 2018). Hence, it has been proposed that negative and positive emotions are not necessarily incompatible in the sense that they can both concern approach action tendencies (e.g., running toward something in happiness, fighting someone in anger; Krieglmeyer & Deutsch, 2013;O'Toole & Mikkelsen, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…This actualizes the question of whether it suffices that action tendencies are incompatible in terms of type of motivational impetus (i.e., approach vs. avoidance) for a counteractive effect to appear. To test this, it would be relevant to look at the possible counteractive effect of fear or anxiety on anger and vice versa, since these emotions, although involving opposite action tendencies (i.e., avoidance vs. approach), could be said to involve shared physiology (Prather, 2018;Siegel et al, 2018), and, at least in some instances, the same motivational context (i.e., threat;O'Toole & Mikkelsen, 2021). In this regard, Zhan et al (2015) found that fear did not counteract anger.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation